Identification of microplastics in milkfish (Chanos chanos) in tradisional ponds in Pedaleman Village, Serang Regency - Ramadhanti, Nadifa Aulia Nur; Hermawan, Dodi; Aryani, Desy (Arwana: Jurnal Ilmiah Program Studi Perairan, 2024)
The entry of microplastic waste into pond waters come from household and fishing activities. This study aims to identify the presence of microplastics in milkfish in the Pedaleman Village pond by considering the type, color, and size of microplastics and to determine the polymers structure found in the digestive tract of milkfish. A total of 24 samples were collected directly from the pond in March to April 2023. The fish were measured for length (cm) and weight (g), and then dissected to remove the organs including digestive tract and muscle. The organs were then destroyed and microplastics were identified using microscope stereo. The fish organs were destroyed using 10% KOH after wet weight was measured. The sample were incubated for 24 hours until the organic matter was destroyed. Then, filtered using Whattman 42 paper and dried in an oven. The types of microplastics found in milkfish were fibers, films, and fragments. Fragment were the most abundant type of microplastics, followed by fiber and film. The fiber had a variety of colors, while the fragments are only found in black. The types of microplastic polymers found in milkfish intestines were polyethylene (PE), polytetrafluoroethylene (PTPE), Polymethyl methacrylate (PMMA), and nylon.